An Italian period on the history of radio engineering’s term “Antenna” - Slyusar, V. І. (Видавництво Львівської політехніки, 2012)
In this article are analyzed a results of research about an italian period on the history radio engineering’s term “antenna”.
Keywords: antenna; Felice Pasetti; Angelo Banti